Urinary excretion of phthalates and paraben after repeated whole-body topical application in humans - Janjua, Nadeem Rezaq; Frederiksen, Hanne; Skakkebæk, Niels E; Wulf, Hans Christian; Andersson, Anna-Maria (International journal of andrology, 2008)
Diethyl phthalate (DEP), dibutyl phthalate (DBP) and butyl paraben (BP) are man-made chemicals used in personal care products, such as lotions and creams. Exposure to these chemicals causes a variety of adverse reproductive outcomes in animal studies. Humans can be exposed to these chemicals through dermal absorption, but there are no published data on absorption, metabolism, and excretion after dermal application. This study investigates urinary concentrations of BP and metabolites of DEP and DBP after topical application. In a 2-week single-blinded study, 26 healthy Caucasian male subjects were given a whole body topical application of basic cream 2 mg/cm² (control week) and then a cream containing 2% (w/w) of DEP, DBP and BP each (treatment week) daily. Twenty-four-hour urine samples were collected. Urinary total, and unconjugated BP, monoethyl phthalate (MEP) and monobutyl phthalate (MBP) metabolites were analysed by Liquid Chromatography-Tandem Mass Spectroscopy (LC-MS/MS). All 26 subjects showed increased excretion of MEP, MBP and BP following topical application. Total MEP, MBP and BP (mean ± SEM) excreted in urine in the treatment week were, respectively, 41 ± 1.9, 11.8 ± 0.6 and 2.6 ± 0.1 mg/24 h. On average 5.79, 1.82 and 0.32%, respectively, of the applied DEP, DBP and BP could be recovered in urine as MEP, MBP and BP. The concentration of the compounds peaked in urine 8-12 h after application. The fractions of unconjugated MEP, MBP, and BP were 78, 8.0 and 2.1%, respectively. Absorption of DEP, DBP and BP through skin could potentially contribute to adverse health effects. The three chemicals are systemically absorbed, metabolized and excreted in urine following application on the skin in a cream preparation. More DEP than DBP was absorbed, presumably because of a faster absorption rate for DEP.